(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to explore the role of e-health in the Saudi Ministry of Health and how it contributes to achieving the goals of the national transformation, with a focus on the quality of healthcare, alignment with Vision 2030, and enabling digital transformation. The quantitative methodology was adopted in this study, where data were collected from a sample of 160 participants. The results showed that e-health contributes significantly to improving the quality of healthcare, but the relationship between e-health and the goals of Vision 2030 and digital transformation needs to be strengthened. The results of the analysis of variance and other statistical tools also showed that there is a need to increase the integration between e-health and the goals of the national transformation by improving the digital infrastructure, training health personnel, and developing digital health policies. Accordingly, several recommendations were made, the most important of which are enhancing the integration between e-health and Vision 2030, improving the digital infrastructure, and stimulating innovation in health technology.